Kakeibo: A Japanese Family Financial Management to Create An Entrepreneurial Family - Arum Pujiastuti; Gilang Kharisma Putra; Shofiatul Mila (Indonesian Journal of Devotion and Empowerment, 2023)
The community service activities carried out in fulfilling the Tridharma of Higher Education focused on training in family financial management in Sidorejo Village, Brangsong District, Kendal Regency, with female participants who are members of the PKK. This activity was carried out to improve community welfare through family financial management using the Kakeibo method (household financial record book). Training is carried out through lectures, demonstrations, and budgeting practice. The results of this community service show that participants are very enthusiastic about participating in the training. Furthermore, by carrying out this activity, participants are expected to manage family finances effectively and efficiently in improving their welfare and creating a financially productive family. The limited time in this activity made the material less detailed; hence, it was necessary to carry out further activities to determine the implementation of the participants' training material. Kegiatan pengabdian masyarakat yang dilakukan dalam memenuhi Tridharma Perguruan Tinggi ini berfokus pada pelatihan pengelolaan keuangan keluarga di Desa Sidorejo, Kecamatan Brangsong, Kabupaten Kendal dengan peserta ibu-ibu yang tergabung dalam PKK. Kegiatan ini dilakukan sebagai upaya peningkatan kesejahteraan masyarakat melalui pengelolaan keuangan keluarga dengan metode kakeibo (buku catatan keuangan rumah tangga). Pelatihan dilakukan dengan cara ceramah, demontrasi, dan praktik pembuatan anggaran. Hasil pengabdian ini menunjukkan bahwa peserta sangat antusias mengikuti pelatihan. Lebih lanjut, dengan dilaksanakan kegiatan ini, para ibu diharapkan mampu mengelola keuangan keluarga dengan efektif dan efisien dalam peningkatan kesejahteraan dan mampu menciptakan keluarga yang produktif dalam keuangan. Keterbatasan waktu dalam kegiatan ini membuat kurang tersampainya materi secara detil sehingga perlu adanya kegiatan lanjutan untuk mengetahui penerapan materi pelatihan yang dilakukan oleh peserta.